Pelletized Slag Cement: Hydraulic Potential and Autoclave Reactivity - Hooton, Douglas Robert (My University, 1981)
With the current pressures to conserve energy and protect the environment, research to take advantage of the cementitious nature of vitreous pelletized blast furnace slag (a byproduct of the steel industry) should yield both economic and technical advantages to the Canadian construction industry.
Three specific areas were chosen for study.
1. The development of a test method to quantify the degree of vitrification achieved in the quenching of blast furnace slags (a property known to have fundamental influence on its reactivity) and the evaluation of new and existing test methods with regard to simplicity and accuracy for potential use as a basis for commercial quality control.
2. The study of the incorporation of slag cement in autoclaved binders having a wide range of compositions in the ternary system containing slag, portland cement and ground quartz (silica flour).
3. The effects of variations in the physical and chemical properties of slag cement on autoclave reactivity.
Within the previously defined areas, a few of the findings are given.
1. From analysis of glass content determinations, the method adopted is critical to the results obtained. The McMaster Individual Particle Analysis was found to give the most accurate and reliable glass content values when compared to a QXRD standard procedure and when used to predict strength potential.
2. Optimum strengths were obtained with ternary slag-portland cement-silica flour binders containing 60 to 75 per cent slag. When autoclaved 4h at 185°C, high strengths corresponded to the presence of semi-crystalline C-S-H resulting in fine pore size distributions, and mixtures of C-S-H and ∝C₂SH. It was also found that slag was activated by silica flour alone resulting in high compressive strengths, high tensile to compressive strength ratios and relatively well crystallized tobermorite.
3. The degree of vitrification of slag was found to have the most significant influence on strength of autoclave cured pastes but the trend was not clear at high glass contents. The CaO and MgO contents were significantly related to strength when combined with the degree of vitrification. However, for evaluating slag hydraulicity, it is suggested that only physical strength testing has the authority for engineering decision making.
Keywords: Civil Engineering; Civil Engineering